Analisis Penerapan Process Standard Offset pada Mesin Cetak Lembaran di PT. Percetakan Gramedia Cikarang - Galingging, Rumbel; Triyanto, Triyanto (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2017)
The development of printing industry are faster on the digital printing and the Internet are moving online world. This would erode offset printing and industrial markets, is a challenge for the field of printing offset printing media. Steps to answer the challenge was the implementation of Process Standard Offset is expected to maintain the quality is guaranteed and applies to the entire world. ISO 112647â€2 is standard for Offset where PT. Percetakan Gramedia Cikarang already certified for the process. But still encountered obstacles during implementation so that raises the question, whether the application of the Offset Standard PROCESS there are irregularities? So of writing this study can find problems in the application of Process Standard Offset. In this quantitative research data collection taken from the prints in order â€œAâ€ in the machine KBA Rapida 105 on Coated paper with this parameter measurements on paper color, ink color, dot gain and measured at the color bar and dot step. So that the figures obtained Î”E * and dot gain deviations when compared with ISO 12647â€2. From the analysis of the measured data was found deviations in color and dot gain control, so we need to make improvement to keep the appropriate level of quality expected by the customer.